Struggle Of Love In Jane Austen Novel " Emma" (1994): AnIndividual Psychological Approach - Setitowati, Tri Mulyo; , Drs. Abdillah Nugroho, M. Hum; , Siti Fatimah, S. Pd, M. Hum (2014)
Problem of the study is how effort of Emma Woodhouse as major character is reflected Emma novel based on structural analysis and individual psychological analysis. This study is qualitative study, object this study focuses on the major character in Emma novel namely Emma Woodhouse. Type of the data of the study is text taken from two data source: primary and secondary. The primary data source us the main data obtain from the Emma by Jane Austen's. Secondary data source is the supporting data are the some materials and references related the study. The technique of data analysis is descriptive analysis. The result of the study shows that : firstly, the structural analysis of the novel consist of character and characterization, setting, plot, point of view, style, theme are related into solid unity. Secondly, the individual psychology analysis shows that some problem of the major character cause of her struggle and then develop to become contradiction between inferiority feeling, striving to superiority, creative self, style of life, social interest, functional finalism and it bring her to the struggle.